THE EFFECT OF QUANTITY AND QUALITY OF VARIETY PRODUCTS AND SERVICE ADVANTAGES ON STUDENTS' SAVE ATTRACTION - Mery Lani Purba; Rika Meihayani Ginting; Tia Novira Sucipto (SEAN Institute, 2022)
Intense business competition in the banking sector requires banks to have strategies and a variety of services. Students are important customers for banking. The aim of this research is to find out the effect of the quantity of product types, service quality, on students' interest in saving at PT. BPR Pijer Podi Kekelengen. The research method is quantitative. Data collection techniques by filling out a questionnaire. Sampling using the incidental method, namely a sampling technique based on coincidence, coincidentally meeting directly with students who are customers of PT. BPR Pijer Podi Kekelengen. The number of respondents was 81 students. Data analysis with validity test, reliability test, normality test, heteroscedasticity test, linear regression analysis, coefficient of determination test, f test and t test. The results of the study show that the quantity of product types has a positive and significant effect on customers' interest in saving, in this case students, to save with significant value, while the quality of service has a positive and significant effect on students' interest in saving. Thus, the quantity and quality of product variety and service excellence have an effect on students' interest in saving.